Tiktok Shop Sebagai Teknologi Pemasaran dan Penjualan Digital Untuk UMKM - Surachman, Adhie; Darmawan, Arief; Tresnawati, Amilia (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
The development of digital communication technology used in business has enabled marketing or sales as a form of digital economy that no longer requires face-to-face meetings. The growth of Indonesia's digital economy is largely supported by the e-commerce sector, which is around 34% or equivalent to IDR 1,900 trillion in 2030. As the digital economy grows, the penetration of Internet users in Indonesia is also increasing. The